Penerjemahan Kutipan di dalam Karya Sastra: Menjembatani Kesenjangan Pengetahuan Skematis - Jaya, Doni (Jurnal Penerjemahan, 2017)
Literary translation is a challenging enterprise because the translator needs to balance between accuracy and conciseness for the sake of beauty. One of the most challenging types of translation unit in literary translation is quotations, especially those which appears in the ST without sufficient information. The challenge lies in the schematic divergence between the ST and TT readers: ST readers can more readily identify the source, meaning, and relevance of the quotation to the narative context, while TT readers cannot. This research was performed to examine the strategies used for translating quotations in a classic novel, as well as the reasons for their application and their impacts on the resulting TT. A number of translation units in the form of quotations and their respective descriptions are proposed as examples. Data consist of ten couples of ST and TT which were taken from Bram Stoker’s Dracula and its Indonesian translation by Ny. Suwarni A. S. Analysis shows that quotations were translated using transference, transference with a footnote, literal equivalent, paraphrase, functional equivalent, and omission, while descriptions were translated using literal equivalent, expansion, synonym, and omission. This research generated several main results. Firstly, translation of quotations is dominated by the ideology of domestication which was employed to reduce the schematic divergence. Secondly, each strategy has its own positive and negative impacts on the TT. For example, omission and paraphrase enhance TT’s coherence and naturalness, but they also eliminate the unit’s characteristic as a quotation and reduce its poetic effect. In conclusion, a translator of quotations in a literry work must take account of various factors, such as schematic gap, poetic effect, exoticism, coherence, and the relative importance of the quotiations. Keywords: literary translation, schematic knowledge, quotation, domestication, foreignization